(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This article analyzes the historical formation of juice production enterprises, their development stages, and the process of transformation into modern industry. It discusses the changes in juice production methods from ancient civilizations to the industrial revolution, technological advancements, and contemporary production processes. Additionally, the current state and prospects of the juice production industry in Uzbekistan are examined.